Planning Meals: Use a Shopping List - Claudia Peñuela (EDIS)
FCS8933, a 2-page fact sheet by Claudia Peñuela, encourages shoppers to make a shopping list before going to the store, and use it while at the store. Includes two sample shopping lists. Published by the UF Department of Family Youth and Community Sciences, November 2010.